Kerangka Kerja Evaluasi dalam Menentukan Kendaraan Kargo yang Optimal Menggunakan Analytic Hierarchy Process - Setiawan, Santoso; Sulistyowati, Daning Nur (LPPM, 2023)
This research aims to develop an evaluation framework in determining the optimal cargo vehicle (freight transportation) using the Analytic Hierarchy Process (AHP) method. The selection of the right cargo vehicle is crucial in logistics management to ensure the efficiency and sustainability of business operations. This research, combines the AHP approach with multi-criteria evaluation to help make better decisions. The proposed evaluation framework consists of several steps, namely: determining relevant criteria in cargo vehicle selection, including factors such as reliability, fuel efficiency, and vehicle price. Then collecting data related to these criteria from reliable sources. Next, conduct a pairwise comparison analysis with AHP to obtain the relative weight of each criterion. And finally calculate the relative performance value for each cargo vehicle based on the set criteria. In this study, the authors applied the proposed evaluation framework to a logistics operation case study. The results show that the use of the AHP method in cargo vehicle selection can help make more systematic and objective decisions. This evaluation framework also allows stakeholders to identify the cargo vehicle that best suits their needs.